Design of Real-Time System Based on Machine Learning for Snoring and OSA Detection - Luo, Huaiwen; Zhang, Lu; Zhou, Lianyu; Lin, Xu; Zhang, Zehuai; Wang, Mingjiang (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2022)
Obstructive sleep apnea (OSA) is a common sleep disorder. The diagnosis of OSA based on snoring is low-cost, convenient and non-invasive. In this study, we place a microphone under the patient's bed and combined with full-night polysomnography to record audio signals. Five machine learning models and two OSA diagnostic schemes are used to classify night audio as non-snoring, snoring, or OSA-related snoring. Our experiment has achieved good results, and the highest diagnosis rate of OSA can reach 97%. Based on the trained classification model, we design a system that can diagnose OSA in real-time. Tests on the system show that it can diagnose apnea by detecting OSA-related snoring. We hope that this approach can develop into a new tool to help a large number of potential OSA patients understand their sleep health.